Lymphoproliferation and hyper-IgM as the first manifestation of activated phosphoinositide 3-kinase δ syndrome: A case report - Mónica Fernandes-Pineda; Andrés F. Zea-Vera (Biomédica: revista del Instituto Nacional de Salud)
Activated phosphoinositide 3-kinase δ syndrome is an inborn error of immunity due to mutations within the genes responsible for encoding PI3Kδ subunits. This syndrome results in an excessive activation of the phosphoinositide 3-kinase signaling pathway. Gainof-function mutations in the gene PIK3R1 (encoding p85α, p55α, and p50α) lead to the development of the activated PI3K δ syndrome. Notably, the clinical presentations of this syndrome often closely resemble those of other primary immunodeficiencies. We present a case involving a 15-year-old male who displayed an immunological phenotype that bore a striking resemblance to hyper-IgM syndrome. Whole exome sequencing was undertaken to pinpoint the underlying genetic mutation. Our investigation successfully identified a heterozygous splice site mutation previously reported within the well-established hotspot of the PIK3R1 gene (GRCh37, c.1425+1 G>T). The diverse spectrum of inborn errors of immunity underscores the pivotal role of identifying gene mutations, particularly in patients presenting clinical manifestations spanning autoimmune disorders, lymphoproliferative conditions, and antibody deficiencies. Such precise genetic diagnoses hold significant potential for improving patient care and management.